PENERAPAN MODEL PEMBELAJARAN KOOPERATIF MIND MAPPING BERBASIS MEDIA AUDIO VISUAL PADA MATERI KUBUS DAN BALOK - Ana Istiani; Siti Rahayu (Universitas Muhammadiyah Kotabumi, 2017)
The purpose of this research was to know: (1) there is difference of mean of result of student's mathematics learning on cube and block material whose learning apply cooperative mind mapping model based on audio visual media and without audio visual media, (2) average result learning mathematics of students on the material of cubes and blocks learning to apply cooperative learning model mind mapping based audio visual media greater than the average learning outcomes of students learning mathematics applying cooperative mind mapping learning model. The population in this study were VIII class students even semester SMP Negeri 1 Sukoharjo academic year 2015-2016, sampling using sampling technique and obtained samples of two classes. This study involves only one variable that is the result of learning mathematics in cube and beam material, consisting of two samples that is the result of learning mathematics of students whose learning applying cooperative learning model mind mapping based on audio visual media as sample 1 and the result of learning mathematics of students whose learning apply cooperative learning model mind mapping as sample 2 obtained through the test of mathematics learning result given to sample 1 and sample 2 in the form of description test. Technique of data analysis using quantitative data analysis covering data normality test stage, homogeneity test, t-test, U test one side, conclusion. Based on the results of research concluded that there are differences in the average results of students' mathematics learning on cube and beam material that learning applying cooperative learning model mind mapping based audio visual media and without audio visual media. The average of students' mathematics learning outcomes on cube and beam materials whose learning is to apply cooperative mind mapping model based on audio visual media is greater than the average of mathematics learning outcomes of students whose learning applied cooperative mind mapping model. This is due to mind mapping cooperative learning based on audio visual media provides an opportunity for students to be more active and students become more motivated in the learning process that lures students become more imaginative and creative in developing the potential work of the brain and mindset so that students can think actively, critical, full of ideas, and easy to organize and remember all forms of information conveyed by the teacher.